Impact Participation Activity Sport to Composition Body Teenager - Nunni Noergina; Adang Suherman; Sucipto; Agus Gumilar; Nuryadi (Universitas Negeri Semarang, 2026)
The problem with this research is that it is not yet clear how sports participation affects adolescent body composition, especially in terms of body mass index, body fat percentage, and muscle mass. This study aims to analyze the impact of sports participation on adolescent body composition. The study design used a causal-comparative approach with an ex post facto approach. Respondents were 85 students aged 18–21 years at the Indonesian University of Education, divided into two groups: those who participated in sports activities three times per week and those who only participated once per week for one semester. Body composition measurements were conducted using the Savvy Body Composition Analyzer based on BIA technology to obtain body mass index (BMI) and visceral fat index values. The results of the independent samples t-test showed a significant difference in BMI between the two groups (p = 0.002), where the group with a higher exercise frequency had a healthier BMI value. These findings support the importance of regular and structured sports activities to improve better body composition in adolescents, as well as prevent health risks related to obesity and metabolic syndrome.